Antimicrobial resistance surveillance in the South African public sector. Issue 4 (2nd October 2018) - Perovic, Olga; Ismail, Husna; Schalkwyk, Erika Van
Abstract : Electronic surveillance for antimicrobial resistance was established in 2013 for public sector laboratories and released annually. This article reports susceptibility data on ESKAPE pathogens for 2016.